Navigating the complexity of ecological stability. (19th July 2016) - Donohue, Ian; Hillebrand, Helmut; Montoya, José M.; Petchey, Owen L.; Pimm, Stuart L.; Fowler, Mike S.; Healy, Kevin; Jackson, Andrew L.; Lurgi, Miguel; McClean, Deirdre; O'Connor, Nessa E.; O'Gorman, Eoin J.; et al.
Abstract: Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall 'stability' of the system. Many international bodies, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear definition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientific and policy literature and show that this disconnect is one consequence of an inconsistent and one‐dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multidimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that define many, perhaps all, of the most important elements of global change. We provide recommendations for theoreticians, empiricists and policymakers on how to better integrate the multidimensional nature of ecological stability into their research, policies and actions.